Evaporation of a water drop with a solid opaque inclusion moving through a high-temperature gaseous medium; Technical Physics Letters; Vol. 42, iss. 3 - Antonov D. V. Dmitry Vladimirovich; Volkov R. S. Roman Sergeevich; Piskunov M. V. Maksim Vladimirovich; Strizhak P. A. Pavel Alexandrovich (2016, 2016)
Title screen